1997
DOI: 10.1002/(sici)1098-0997(1997)5:1<10::aid-idog5>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind placebo-controlled treatment trial ofChlamydia trachomatis endocervical infections in pregnant women

Abstract: Objective: The purpose of this study was to determine if treatment of pregnant women with Chlamydia trachomatis infection would lower the incidence of preterm delivery and/or low birth weight.Methods: Pregnant women between the 23rd and 29th weeks of gestation were randomized in double-blind fashion to receive either erythromycin 333 mg three times daily or an identical placebo.The trial continued until the end of the 35th week of gestation.Results: When the results were examined without regard to study site, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 19 publications
3
48
1
1
Order By: Relevance
“…It has been hypothesised that the iron-rich environment of the vagina in menstruating women provides conditions conducive to TV growth and persistence 8. One unique feature of the TV genome is the duplicity for the majority of genes, of which 117 are upregulated in iron-rich environments, and 78 in iron-restricted environments 9.…”
Section: Hormonal Effects As a Major Driver Of Tv Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…It has been hypothesised that the iron-rich environment of the vagina in menstruating women provides conditions conducive to TV growth and persistence 8. One unique feature of the TV genome is the duplicity for the majority of genes, of which 117 are upregulated in iron-rich environments, and 78 in iron-restricted environments 9.…”
Section: Hormonal Effects As a Major Driver Of Tv Epidemiologymentioning
confidence: 99%
“…One unique feature of the TV genome is the duplicity for the majority of genes, of which 117 are upregulated in iron-rich environments, and 78 in iron-restricted environments 9. The presence of iron facilitates the adherence of TV to the genital tract epithelium 8. This feature may facilitate survival of the parasite in iron-rich environments, like the vagina in menstruating women, where haeme from the breakdown of menstrual blood provides an abundant supply of iron.…”
Section: Hormonal Effects As a Major Driver Of Tv Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…A single trial of treatment for reproductive tract infection due to chlamydia failed to reduce the risk of preterm birth. 355 In a recent review of the impact of treatments for bacterial vaginosis, Joesoef et al 347 concluded that women with symptomatic disease, whether pregnant or not, should be treated with metronidazole (500 mg, twice daily, for 7 days), clindamycin vaginal cream (2%, once daily as a nocturnal intravaginal application, for 7 days), or metronidazole vaginal gel (0.75%, twice daily, for 4 days), because these regimens have produced equivalent cure rates. For pregnant women with high risk of an adverse pregnancy outcome (ie, those with a prior preterm birth) but asymptomatic disease, intravaginal clindamycin is not recommended, because it has failed to reduce rates of preterm births.…”
Section: Antibiotics For Bacterial Vaginosismentioning
confidence: 99%
“…6272 Moreover, randomized clinical trials have been undertaken to test the effect of antibiotics in patients with bacterial vaginosis (BV), 73–87 Trichomonas vaginalis , 88 group B streptococci (GBS), 89,90 Ureaplasma urealyticum , 91,92 and Chlamydia trachomatis. 93 …”
mentioning
confidence: 99%